Peran Wanita Pedagang Sayuran Terhadap Pendapatan Rumah Tangga di Kabupaten Kotawaringin - Putra, Ma'sum Aji Malvino; Winarti, Lili (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Female vegetable traders work to supplement household income. Despite their husbands being employed, their independence drives them to contribute financially. The average income of the husbands, around Rp 4,000,000, is insufficient to support a family of four. Consequently, many women engage in informal work, such as trading, to earn additional income for their families. This study aims to analyze the characteristics of female vegetable traders and their role and contribution to the family income. The research is conducted in Subuh Market, Alkamal Market, and Keramat Market, Kotawaringin Timur Regency, Central Kalimantan Province, selected purposively. The study involves 50 married female vegetable traders, with samples taken using purposive sampling. Primary data is collected through interviews, while secondary data is gathered from BPS, journals, and other relevant sources. Results show that the majority of the female traders are aged 31-40 years (46%), have a primary school education (42%), and have more than four years of trading experience (56%). Most have four dependents (46%). The role and contribution of these female traders to household income is 43.8%, with an average income of Rp 3,395,000 per month. It can be concluded that the contribution of female vegetable traders to family income is relatively small, as it is less than 50%.